Ubimus post-2020: Creative Strategies in Contracapas and Ouija (Revista Argentina de Musicología, 2022)
We discuss the impact of the pandemic on post-2020 musical activities. We propose the ubimus (ubiquitous music) approach as a theoretical and methodological framework that, on the one hand, encourages aesthetic flexibility and, on the other, proposes the intensive use of everyday spaces, broadening the profile of potential participants and creators. In order to support our proposed concepts, we present two case studies implemented by members of the Amazon Music Research Center (NAP): Contracapas and Ouija. Contracapas results from the accumulation of “layers” (capas) of texts and processed musical fragments, which function as an alternative mechanism to simultaneous interaction. Ouija proposes a practical reflection on the impact of remote interaction when sonic communication is not available. Both proposals arise as a response to the pandemic situation and share technical and conceptual solutions with a solid foundation in ubiquitous musical practices.
Keywords: Ubiquitous music; Ubimus; NAP; Pandemic; Social isolation